Evaluation of stiffness values of normal uterine myometrium by 3T magnetic resonance elastography - Karakaş, Levent; Poçan, Süheyl; Şahin, Şükrü (Frontiers in Medicine, 2026)
BackgroundThere is not enough radiologic data in the literature for the quantitative value of uterine stiffness and this study aims to contribute to the literature in this field.ObjectiveTo evaluate the feasibility of measuring uterine myometrial stiffness (UMS) using 3T magnetic resonance elastography (MRE) in women with radiologically normal uteri and to explore potential associations with demographic and anatomical variables.MethodsData on demographics, including age, BMI, obstetric history (gravida and parity), menopausal status, and oral contraceptive use, were gathered. Uterine measurements, such as the long axis, transverse diameter, anteroposterior diameter, and volume, were obtained using 3T MR imaging. UMS (in Pascals) was quantified using MRE, and its associations with various factors were assessed. Values are reported as mean ± standard deviation (SD).ResultsThe study enrolled 48 women with a mean age of 37.54 ± 10.47 years. The average UMS was 2714 ± 300 Pa. A strong positive correlation was found between age and UMS (r = 0.814, p < 0.001), whereas no significant associations were found with BMI, uterine dimensions, gravida, or parity. UMS was higher in postmenopausal women than in women of reproductive age (p < 0.001). However, no statistically significant differences were observed between oral contraceptive users and non-users in this limited sample.ConclusionThis feasibility study demonstrates the practicality of assessing uterine myometrial stiffness using 3T MRE and provides exploratory estimates in radiologically normal uteri. Larger prospective studies are required before normative ranges can be established.